Efficacy of Transcranial Magnetic Stimulation in Post-Stroke Motor Recovery: Impact of Impairment Severity - Guiyuan Cai; Cailing Zhang; Jiayue Xu; Junbo Jiang; Gengbin Chen; Jialin Chen; Quan Liu; Guangqing Xu; Yue Lan (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Stroke is a leading cause of impairment, with 70% of survivors experiencing upper limb motor deficits. While transcranial magnetic stimulation (TMS) is widely used in rehabilitation, the impact of impairment severity on treatment outcomes remains unclear. This study evaluated TMS effectiveness in post-stroke motor impairment and explored its neural mechanisms. Fifty-five stroke patients were divided into TMS (n =27) and control (n =28) groups. The TMS group received two weeks of intermittent theta-burst stimulation (iTBS), while controls received sham stimulation. Patients were stratified into mild/moderate (Fugl-Meyer Assessment [FMA] $\ge 30$ ) and severe (FMA <30) impairment subgroups. Motor function and electroencephalography (EEG) metrics were assessed before and after treatment. Overall FMA improvement showed no difference between groups, but the TMS-mild/moderate impairment group demonstrated significantly greater improvement compared to others. This group exhibited higher global and local alpha band power and global alpha efficiency. FMA improvement positively correlated with local alpha power changes. TMS of ipsilesional M1 improves motor function in mild/moderate impairments but shows limited efficacy in severe cases. EEG suggests TMS promotes recovery by modulating alpha activity and enhancing network efficiency. These findings support stratified treatment approaches and highlight the need for alternative interventions in severe impairment.